Stereotypes of the Christian Citizen towards the other a Sample of Christian Citizens in Baghdad - Ali, Anwer Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
The research aimed to know stereotypes perceptions of the Christian citizen towards the other. The sample consisted of (84) of the Iraqi Christian citizens who live in the city of Baghdad of both genders. Their ages ranged between (18-50) years, with an average of (21) years. A scale designed for this purpose meets all requirements for psychometrics. It consisted of (24) paragraphs, measuring the concept of stereotypical perceptions towards the other, and the psychometric properties of it were calculated, and the degree of reliability reached an alpha equation (0.78). The results of the research showed that the perceptions held by the members of the sample are positive towards other groups.